The Students' Difficulties in Enriching Vocabulary and Its Techniques to Overcome the Difficulties - Devie Reztia Anjarani; Yuliarsih; Evha Nazalatus Sa'adiyah Sy (Penerbit STKIP PGRI Bangkalan, 2022)
Enriching vocabulary looks easy, but it is possible that students encounter difficulties in enriching vocabulary. The purpose of this study is to find out the difficulties faced by students in enriching vocabulary, and also to investigate what strategy can be applied to overcome those difficulties. Researcher used qualitative-descriptive method as method in describing the data by applying three methods and the instruments. They are observation, interview, and documentation. The result of study showed students complained about pronunciation, unfamiliar words, and memorize as their difficulties in enriching vocabulary. While techniques to overcome that difficulties, they are word list and song that is applied by students and modification of memorize that is applied by teacher. Students are expected to manage the way of learning, and also what will they do to avoid the possibility of difficulties they can face.